Interpretation of Qur'anic Economics with a Thematic Tafsir Approach in Addressing the Surge of Fraud and Digital Crimes on Social Media - Mukhtar Yunus (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The social security and economic stability of Indonesian society are seriously threatened by the increase in fraud and cybercrime on social media in 2024. In Indonesia, where 78.19% of the population uses the internet, online fraud, phishing, investment schemes, and illegal activities through digital platforms are increasingly rampant. To build an ethical foundation in tackling the increase in fraud and cybercrime on social media, this study seeks to understand the economic values ​​of the Quran using thematic interpretation techniques. This qualitative study uses the thematic interpretation approach (al-tafsīr al-mawḍū'ī), which collects Quranic verses related to business ethics, transactions, and economics for thematic analysis. The fundamental economic principles contained in the Quran include: (1) transparency in transactions and honesty (al-ṣidq); (2) justice (al-'adl) and balance; (3) prohibition of exploitative practices and usury (al-ribā); (4) trust (al-amānah) in asset management; and (5) the consequences of accountability in this world and the hereafter. It is believed that a digital economic environment with integrity can be built by applying these principles within the framework of digital governance and literacy. In addition to offering useful suggestions for the government, social media companies, and the general public in developing Al-Qur'anic economic literacy as a deterrent to cybercrime, this study provides a theoretical contribution to the integration of interpretation with cybercrime studies.